2020
DOI: 10.1029/2019ea000966
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 Mw 7.5 Papua New Guinea Earthquake: A Possible Complex Multiple Faults Failure Event With Deep‐Seated Reverse Faulting

Abstract: Although the Papuan fold and thrust belt (PFTB) is thought to accommodate convergence between the Pacific and Australian plates, the possible strain partitioning and its kinematic controls in the region are poorly understood. On 25 February 2018, a devastating Mw 7.5 earthquake jolted the southern area of the PFTB, central Papua New Guinea. The detailed imaging of the source parameters of this large earthquake is an urgent demand for a better understanding of the tectonism in the region. Here we used spaceborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…One of the advantages of the InSAR technique is that it provides a widespread and mostly continuous map of ground deformation. The distribution of earthquakes relative to LOS displacement (i.e., earthquakes mostly located to the South-SW) suggests that ground deformation was related to hanging wall uplift (e.g., fault-related folding) along NE-dipping fault planes-which is consistent with moment tensor and finite-fault model solutions (USGS, 2018;Wang et al, 2020;Zhang et al, 2020). We interpret at least five distinct zones of ground deformation based on GPS measurements and the ascending and descending interferograms published on the GSI website (GSI, 2018), along with an abundance of small-scale features that may represent surface ruptures such as fissures or scarps.…”
Section: Crustal Deformationsupporting
confidence: 71%
“…One of the advantages of the InSAR technique is that it provides a widespread and mostly continuous map of ground deformation. The distribution of earthquakes relative to LOS displacement (i.e., earthquakes mostly located to the South-SW) suggests that ground deformation was related to hanging wall uplift (e.g., fault-related folding) along NE-dipping fault planes-which is consistent with moment tensor and finite-fault model solutions (USGS, 2018;Wang et al, 2020;Zhang et al, 2020). We interpret at least five distinct zones of ground deformation based on GPS measurements and the ascending and descending interferograms published on the GSI website (GSI, 2018), along with an abundance of small-scale features that may represent surface ruptures such as fissures or scarps.…”
Section: Crustal Deformationsupporting
confidence: 71%
“…Based on the InSAR data, Wang et al (2020) suggested that the 2018 M W 7.5 PNG earthquake may rupture four faults ( Figure S14) with a fault step over larger than approximately 10 km. Whether an earthquake rupture can jump a large fault step of over 10 km remains unsolved.…”
Section: /2020gl089271mentioning
confidence: 99%
“…Readily observable field evidence of only the largest or most recent natural disasters typically persists in temperate environments due to the constant regrowth cycle of vegetation. Locating this field evidence and determining historical patterns of natural disasters is a primary objective for many agencies and communities (Paton and Johnston, 2001;Wegmann, 2006;Brand et al, 2019). However, fieldwork is often inefficient and expensive compared to remote sensing methods and it does a poorer job at temporally constraining natural disasters.…”
Section: Introductionmentioning
confidence: 99%